INTERCOMPRENSIÓN LINGÜÍSTICA EN EL PERÚ: ALGUNOS APORTES PARA SU ESTUDIO - Romani Miranda, Maggie (2011)
This article introduces some aspects of the linguistic Intercomprehension methods developed in Europe and in Latin America for simultaneous language teaching. These methods were taught to the members of the intercomprehension linguistic team of Universidad Ricardo Palma during their linguistic training in Chile. This activity was coordinated by Dr. Luis Miranda Esquerre. Those aspects emphasize the importance of developing a linguistic intercomprehension method for the teaching of american indian languages in Perú.